The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1115/1.4041073
|View full text |Cite
|
Sign up to set email alerts
|

Central Composite Experimental Design Applied to the Dry Sliding Wear Behavior of Mg/Mica Composites

Abstract: A five-level four-factor central composite design multivariable model was constructed for the evaluation of the combined effect of operating parameters such as percentage reinforcement (0–10%), load (5–25 N), sliding speed (1–5 m/s), sliding distance (500–2500 m) on the wear rate of mica reinforced metal matrix composites. The microwave-assisted powder metallurgy technique was used to fabricate the composites. The wear tests were performed according to statistical designs to develop an empirical predictive reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The CCD is the most preferred response surface experimental design for fitting the quadratic models. The general form of a response surface model based on CCD can be written, as shown in equation (2) [40].…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…The CCD is the most preferred response surface experimental design for fitting the quadratic models. The general form of a response surface model based on CCD can be written, as shown in equation (2) [40].…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…The results indicated that dual ceramic reinforcement composites had better wear resistance than single ceramic reinforcement composites. Raj et al 16 used central composite design for the different levels of considered operating parameters such as load (5-25 N), reinforcement percentage (0-10%), sliding distance (500-2500 m) and sliding speed (1-5 m/s). The input parameters such as weight percentage of reinforcement and sliding distance were found to play a significant effect on wear rate.…”
Section: Introductionmentioning
confidence: 99%
“…Particle size, followed by reinforcement size, was the most vital factor in wear. However, it was noted that the sliding distance and load had an insignificant effect (John Iruthaya Raj et al, 2019).…”
Section: Introductionmentioning
confidence: 99%